2009
DOI: 10.1007/s00572-009-0241-6
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous arbuscular mycorrhizal symbiosis of yam (Dioscorea spp.), a key staple crop in West Africa

Abstract: Yam (Dioscorea spp.) is a tuberous staple food crop of major importance in the sub-Saharan savannas of West Africa. Optimal yields commonly are obtained only in the first year following slash-and-burn in the shifting cultivation systems. It appears that the yield decline in subsequent years is not merely caused by soil nutrient depletion but might be due to a loss of the beneficial soil microflora, including arbuscular mycorrhizal fungi (AMF), associated with tropical "tree-aspect" savannas and dry forests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 44 publications
(52 reference statements)
1
14
0
2
Order By: Relevance
“…In fact, Glomus is the most widely distributed AMF species and it is considered as cosmopolitan in many ecosystems (SĂ˝korová et al 2007). Tchabi et al (2009) reported that G. etunicatum which is one of the dominant species in this study tend to be a dominant species in soil samples from the yam field sites.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, Glomus is the most widely distributed AMF species and it is considered as cosmopolitan in many ecosystems (SĂ˝korová et al 2007). Tchabi et al (2009) reported that G. etunicatum which is one of the dominant species in this study tend to be a dominant species in soil samples from the yam field sites.…”
Section: Discussionsupporting
confidence: 50%
“…However, as these census data were used to develop global inventories of harvested crop area [20] and cropland extent [21] applied as major input for MIRCA2000, these statistics cannot be used for validation purposes in a strict sense, but show nevertheless the consistency between input data used to develop MIRCA2000 and results derived from the dataset. Furthermore there is also evidence from the literature that shifting cultivation or slash-and-burn farming is practiced in many subtropical or tropical regions that have low cropping intensity and large fallow extent in MIRCA2000 [12][13][14][27][28][29][30][31]. Therefore the general pattern of cropping intensity presented in this study is reasonable, but there is a need to verify it by using independent information, e.g.…”
Section: Comparison To Independent Datamentioning
confidence: 68%
“…Host preference was several times reported from different environments [37][38][39]. On the other hand, trap culture studies with single host plant species revealed that the large majority of AM fungi, present in the soils, could be propagated on single plant species [40,41]. In this respect, it is also notable that, even for specific plant species, differences between intraradical and extraradical AMF communities might exist, although most AMF species prefer to explore the soils and thus, preferentially live and sporulate in the rhizospheric soil environment.…”
Section: Discussionmentioning
confidence: 99%